(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
Тriticale, a hybrid of wheat (Triticum) and rye (Secale), is a promising cereal crop due to its high adaptability to adverse growing conditions, resistance to diseases, and good nutritional properties. However, ensuring the preservation of its grain quality during long-term storage remains a significant challenge. Grain storage conditions, particularly temperature, play a crucial role in maintaining the physical, biochemical, and sanitary indicators of quality. This study aims to evaluate the effect of different temperature regimes – including regulated (+5 °C and –5 °C) and unregulated (ambient room temperature, +25 °C ) – on the primary quality indicators of spring triticale grain during storage over 16 months. The experimental research was conducted using grain samples of different spring triticale varieties: Aist Kharkivskyi, Lebid, Khlibodar, Oberih, Dar Khliba, and Sontsedar. The indicators analyzed included test weight (grain bulk density), thousand-kernel weight, germination energy, and contamination by microscopic fungi, particularly Fusarium, Alternaria, and Penicillium species. The results demonstrated that the regulated temperature regime of +5 °C provided the most favorable conditions for maintaining the quality of triticale grain. In this regime, test weight losses were minimal across most varieties, with changes not exceeding 1-2%, and thousand-kernel weight remained relatively stable. For example, in the Oberih variety, test weight decreased by only 8 g/L over 16 months, while in the Sontsedar variety, it remained almost unchanged. Similarly, germination energy was preserved at high levels – up to 86% in the Dar Khliba variety – indicating good physiological quality and high viability for seed use. Storage at –5 °C demonstrated mixed results. While this low temperature significantly suppressed fungal development – particularly Fusarium spp., which showed a decrease or minimal growth during storage – it also had varied effects on physical and physiological indicators depending on the variety. In some cases, such as the Aist Kharkivskyi variety, a noticeable decrease in test weight was observed, possibly due to the structural effects of prolonged exposure to sub-zero temperatures on the grain. Unregulated storage under ambient room temperature conditions resulted in a steady decline in all analyzed quality indicators. Test weight and thousand-kernel weight decreased significantly across all varieties. Germination energy declined by more than 20% in several samples, and fungal contamination increased substantially, reaching up to 9% Fusarium infection in Aist Kharkivskyi and 8.3% in Khlibodar. These findings confirm that unregulated conditions are unsuitable for the long-term preservation of spring triticale grain. Microscopic fungal contamination is a major factor affecting grain quality during storage. Fusarium was the most dominant pathogenic fungus, especially under unregulated conditions. However, regulated storage at +5 °C slowed down fungal growth, and storage at –5 °C was the most effective in preventing fungal contamination altogether. The species composition of fungi shifted depending on the temperature and storage duration, with Penicillium and Alternaria being present in all regimes but showing less aggressive development at lower temperatures. Overall, the findings of this study confirm that temperature control is a key factor in ensuring the long-term preservation of spring triticale grain. The regulated regime of +5 °C is recommended as the optimal storage condition, ensuring the stability of both physical and physiological grain quality indicators while also limiting microbial contamination. The use of –5 °C storage can be justified when fungal contamination is a major concern, though its application should be tailored to specific varieties due to possible negative effects on structural and germination properties. These results have practical implications for grain storage technologies and can help optimize post-harvest handling strategies for spring triticale in industrial and agricultural settings.